A criança e os artefatos lúdicos: um estudo etnográfico da cultura lúdica da rua - Lima, Francisca Josélia Inocêncio de (2010)
This research, continuing to work “Between hands and machines: the logic of building of playful artifacts”, developed as scientific initiation in degree course, tried to understand the relationship of the children with the industrial playful artifacts and crafts artifacts from the modes of play in a specific cultural context, the street. The corpus was composed of the records of the observations of free playful activities developed by children and adults residents in the Coronel Fabriciano Street, in the Granja Portugal district in the periphery of Fortaleza. The use of the case study in education inspired ethnographic research methodology made possible to realize the cultural peculiarities of to play in the context studied. For the analysis of the corpus, we resorted to theoretical categories: modes of play, appropriated by Costa from manners of make of Cearteau, discourse as conceptualized by Bakthin and playful culture, from the perspective inaugurated by Brougère. The results of this study suggests that the nature of the artifacts and the context in which they organize the playful activities playing an important role in the differentiation of modes of play. However, the initiative of the child makes complex this relationships in that it dialogues child with the multiple discourses that pervade the playful practices partly account for the production of the play culture, acting both in dialogue with the previous generation as in the dissemination between peers.